Arthroscopic Management of Synovial Osteochondromatosis of the Elbow - Chan, Sui Kit (Arthrosc Tech, 2021)
Primary synovial chondromatosis is characterized by newly formed chondral or osteochondral nodules in the synovial membrane, which may detach and form loose bodies. The loose bodies can be calcified or ossified, and the condition is termed synovial osteochondromatosis. Three distinct stages can be identified in primary synovial chondromatosis : phase I is active synovitis without loose bodies, phase II shows nodular synovitis along with loose bodies, and phase III is characterized by the presence of loose bodies with the resolution of synovitis. Surgical treatment has been recommended as the first choice of therapy in phases II and III disease. Complete synovectomy and removal of all loose bodies is advisable for prevention of recurrence of the disease. In this technical note, the technical details of arthroscopic removal of loose bodies and synovectomy for the management of synovial osteochondromatosis of the elbow is described. Compared with open procedures, the arthroscopic approach has many advantages, including a shorter rehabilitation period and higher patient satisfaction.